The Economics of Gender in China Women, Work and the Glass Ceiling - Sung, Sisi (Routledge Studies in Gender and Economics, 2022)
China's rapid socio-economic development has achieved remarkable equalizing conditions between men and women in the aspects of health, education and labor force participation, but the glass ceiling phenomenon has become more prominent. The book develops a cross-disciplinary paradigm, with economics at its core, to better understand gender in China and women in management in the Chinese business context. The theoretical perspective integrates the knowledge and evidence from cognate disciplinary strands, such as economics, sociology, management studies, and the Chinese literature, into one unified framework. In-depth interviews with managers in China's largest enterprises complement the theoretical perspective with rich empirical details to examine women's managerial experiences and career choices. The book's argument sheds light on the power of stereotypes that specify women's roles in the family, organization, and society. It shows that understanding the socio-psychological and organizational dynamics of stereotyping in the Chinese context, as well as how Chinese women make career decisions, recognizing and deploying these expectations, provides new perspectives on the underrepresentation of women among business leaders in China. The book offers multi-disciplinary evidence on the economics of gender in China that is highly relevant for gender studies in general, and across a number of subject areas, and it can be used in any setting as an introductory reference.